Synthetic Approaches to Non-Tropane, Bridged, Azapolycyclic Ring Systems Containing Seven-Membered Carbocycles - Shoemaker, Aaron H.; Griffith, Daniel R. (Synthesis, 2020)
This Short Review highlights various synthetic approaches to bridged azabicyclic ring systems containing seven-membered carbocyclic rings. Such ring systems are common to a number of biologically active natural products. The seven-membered ring in such systems is generally formed in one of four ways: 1) cyclization of an acyclic precursor; 2) ring expansion or rearrangement of a different ring size; 3) cycloaddition; and 4) use of a synthetic building block with the seven-membered ring already present. Representative examples of each approach from both total synthesis and methodological studies are discussed, with an emphasis on work publishedin the last twenty years.1 Introduction2 Cyclization Reactions3 Ring Expansions and Rearrangements4 Cycloadditions5 Strategies Involving Seven-Membered Ring Building Blocks6 Conclusion
Keywords: alkaloids; heterocycles; rearrangements; natural products; cycloheptane; bridged bicyclic